PEMBERDAYAAN MUSTAHIK UNTUK MENJADI MUZAKKI (Studi Kasus: LAZIZMU Keputih) - Umi Atia Hanik (STAI AN-NAJAH INDONESIA MANDIRI, 2020)
This research discusses the empowerment of mustahik to become muzakki which is located at LAZIZMU Keputih. The purpose of this research is to find out how the process of empowering mustahik into muzakki. This research is a type of qualitative research with a descriptive approach. Sources of data used as a reference in this study are books, journals, websites and interviews. The results of this study indicate that the empowerment carried out by LAZIZMU Keputih has succeeded in turning a mustahik into a muzakki in the Ta'awwun Untuk Negeri program by going through a long process from starting to choose who is the target to participate in this program, training, giving carts, giving funds, showing a strategic place for sales and regular monitoring so that he can become a muzakki. Besides that, mustahiks are also encouraged to take part in recitation and do alms every month so that their rizkin is smoother and more abundant and understand how to sell according to Islamic sharia. Keywords: Empowerment, Mustahik and Muzakki